Impacto sostenible en el desarrollo de cantones de la zona este de la provincia del Guayas por la explotación y uso de materiales pétreos locales para la fabricación de hormigón - Lluma Quishpe, Juan Gregorio (2024)
The thesis examined the sustainable impact on the development of cantons in the eastern area of the province of Guayas, focusing on the exploitation and use of local stone materials for the manufacture of concrete. The main findings revealed that the extraction of these materials has generated economic benefits, such as job creation and business stimulation, although it has also posed environmental challenges, including landscape degradation. The importance of community participation in decision-making is highlighted and recommendations are proposed, such as continued research for more sustainable practices, effective regulations, environmental education programs and economic diversification to ensure balanced and sustainable development in the region. The research focused on understanding the impact of the exploitation of local stone materials on the development of the cantons in the eastern area of the province of Guayas, specifically in relation to the manufacture of concrete. This industry is critical to the region's economic growth, but poses significant challenges in terms of sustainability. We could determine as Economic Contribution: The exploitation of local stone materials has generated substantial economic benefits, including job creation and the promotion of business activity in the region........